Ultraviolet photodissociation of gas-phase transition metal complexes: dicarbonylcyclopentadienyliodoiron(II). (17th January 2021) - Hansen, Christopher S.; Marchetti, Barbara; Karsili, Tolga N. V.; Ashfold, Michael N. R.
Abstract : The ultraviolet photodissociation of the prototypical organometallic half-sandwich compound dicarbonylcyclopentadienyliodoiron(II) [ η 5 -CpFe(CO)2 I] has been studied in the gas phase across the wavelength range 260 ≤ λ ≤ 310 nm using multi-mass velocity-map ion imaging with photoproducts detected using both resonance enhanced multiphoton and vacuum ultraviolet ( λ  = 118.2 nm) single photon ionisation methods. Ion images recorded for the atomic iodine and the cyclopentadienyl photoproducts reveal fast, anisotropic components to their recoil velocity distributions. The experimental work is supported by multi-reference (spin–orbit averaged) electronic structure calculations that suffice to illustrate the high electronic state density in such transition metal complexes and provide insights into the rival fragmentation dynamics. The ground state parent molecule has singlet spin multiplicity, but the product energy disposal measured following Fe–Cp bond fission shows the involvement of nominally spin-forbidden transitions. The Fe–I and Fe–Cp bond fissions should both be viewed as homolytic and occurring on excited state potentials that are dissociative in the relevant ligand elimination coordinate. GRAPHICAL ABSTRACT: